การปฏิบัติดานจิตวิญญาณ: การภาวนาอธิษฐานตามแบบคริสตศาสนา - สมกำลัง, พัชนี; ไชยสิทธิ์, ยุทธชัย; อารยะศิลปธร, นาฏยา; คะตา, วิสัย (วารสารพยาบาลศาสตร์และสุขภาพ, 2014)
Nursing is a spiritual practice. The spiritual health of a professional nurse is very important because the spiritual experience of a caregiver has a direct effect on the humanized nursing care. The prayer in Christian tradition is a spiritual practice that includes several important qualities. Prayer brings an interconnectedness with God. Confession and receiving forgiveness is a continuous practice that goes together with meditation on Christian religion doctrines (Holy Bible). These practices lead to wisdom and truth in life which ultimately gives purpose to life. Reflective thinking and self-awareness through prayer is a spiritual practice that provides spiritual needs and ultimately spiritual well-being.